Technological innovations and aggregate risk premiums☆ - Hsu, Po-Hsuan (Journal of Financial Economics, 2009)
In this paper, I propose that technological innovations increase expected stock returns and premiums at the aggregate level. I use aggregate patent data and research and development (R&D) data to measure technological innovations in the U.S., and find that patent shocks and R&D shocks have positive and distinct predictive power for U.S. market returns and premiums. Similar patterns are also found in international data including other G7 countries, China, and India. These findings are consistent with previous empirical studies based on firm-level data, and call for further theoretical explanations.